2018
DOI: 10.1016/j.jid.2018.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Resident T Cells in Resolved Psoriasis Steer Tissue Responses that Stratify Clinical Outcome

Abstract: Psoriasis is driven by focal disruptions of the immune-homeostasis in human skin. Local relapse following cessation of therapy is common and unpredictable, which complicates clinical management of psoriasis. We have previously shown that pathogenic resident T cells accumulate in active and resolved psoriasis, but whether these cells drive psoriasiform tissue reactions is less clear. Here, we activated T cells within skin explants using the pan-T cell activating antibody OKT-3. To explore if T cells induced dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
84
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 49 publications
3
84
0
2
Order By: Relevance
“…These T cells show quite similar profiles to those of T RM in never-lesional psoriatic skin. Here again, the relative expression levels of IL-17A to IFNg and IL-10 in the remaining T cells of the cleared skin turned out to correlate with the duration of remission [35]. It has also been demonstrated that cleared skin after treatment for psoriasis contains T cells with limited diversity in terms of the T cell-receptor repertoire [36].…”
Section: Psoriasismentioning
confidence: 83%
See 1 more Smart Citation
“…These T cells show quite similar profiles to those of T RM in never-lesional psoriatic skin. Here again, the relative expression levels of IL-17A to IFNg and IL-10 in the remaining T cells of the cleared skin turned out to correlate with the duration of remission [35]. It has also been demonstrated that cleared skin after treatment for psoriasis contains T cells with limited diversity in terms of the T cell-receptor repertoire [36].…”
Section: Psoriasismentioning
confidence: 83%
“…The emergence of biologics will enable drastic improvement of psoriasis and disease-free status has become a realistic goal. However, even in cleared skin, IL-17A/ IL-22-producing T cells remain in the epidermis [13,35]. These T cells show quite similar profiles to those of T RM in never-lesional psoriatic skin.…”
Section: Psoriasismentioning
confidence: 91%
“…In contrast, in the dermis of the psoriatic plaques, TRM cells show lower expression of CD103, as demonstrated by Cheuk et al [5]. In the first stage of psoriatic inflammation, in the skin without lesions yet, epidermal TRM cells expressing CCR6 cooperate with CCL20 expressing keratinocytes [35,36].…”
Section: Tissue Resident Memory Cells In Psoriasismentioning
confidence: 87%
“…The optimal treatment time needed to completely silence TRM, which could ensure that there is no recurrence of lesions at the location is unknown [37]. Therefore, psoriatic lesions preferentially recur in previously affected areas of the skin, and pathogenic TRM cells exposed to IL-17A and IL-22 accumulate in resolved lesions [5,35]. In the study of Gallais Serezal et al [38], tissue responses after T cell stimulation in healthy and psoriatic lesions were analyzed.…”
Section: Tissue Resident Memory Cells In Psoriasismentioning
confidence: 99%
“…Activated keratinocytes secrete IL-17C, which activates keratinocytes in an autocrine way. Recently, the contribution of resident memory T cells [5][6][7][8], epidermal dendritic cells [9] in the epidermis, and type 3 innate lymphoid cells [8,10] to the development of psoriasis and recurrent plaque has attracted attention.…”
Section: Plaque Psoriasismentioning
confidence: 99%